Characterization of organic carbon compounds of tropical peat from various land management types - Könönen, Mari; Jauhiainen, Jyrki; Laiho, Raija; Spetz, Peter; Kusin, Kitso; Limin, Suwido; Vasander, Harri (my, 2016)
The carbon chemistry largely determines the decomposability of organic substrate. The advanced knowledge of tropical peat organic carbon chemistry (OCC) improves understanding of carbon dynamics, which is needed for sustainable management of these ecosystems. Yet, tropical peat OCC is a highly understudied subject. To study tropical peat OCC we gathered samples for undrained peat swamp forest and three other land uses altered 20-30 years prior to the study, which together form a continuum of increasing land-use intensity. From studier peats collected from In Central-Kalimantan, Indonesia, the OCC, i.e. the hemicellulosic carbohydrate and uronic acid compositions and concentrations of extractives, cellulose, acid-soluble lignin and acid-insoluble residue were determined. With this study we aim to answer the following questions: (i) Does land-use change affect tropical peat OCC? (ii) How does land-use change affect OCC? (iii) What kind of implications could changes in OCC cause to carbon dynamics at various land use types?
Keywords: tropical peat; land-use; decomposability; peatlands; degradation; carbohydrates; polymers